Using word cross game to impprove students’ vocabulary learning at SMK Muhammadiyah 1 Yogyakarta - Hilda Andira Nugraheni; Umi Rokhyati (Teaching English as a Foreign Language Journal, 2022)
This research was conducted at SMK Muhammadiyah 1 Yogyakarta. Based on the experience during the teaching practicum, it was identified that students still got problem with their vocabulary. It caused them afraid to speak English and feeling embarrassed if the word or sentence they conveyed was wrong. They also have little effort to read or look up the dictionary to know the new words. In addition, students easily got bored when learning in a conventional way. There is a problem in learning vocabulary. Based on those problems, classroom action research was conducted with two objectives: to describe the increase of students’ interest and vocabulary mastery taught using the word cross game. The subject of the research was a class consisting of 21 students. To collect the data, observation, test, and interview were done. Mixed methods were used to analyzed the data. The research was conducted in two cycles. Each cycle followed the steps of planning, acting, observing, and reflecting. The research findings revealed that the students’ interest in learning increased. They stated that learning using cross word games is fun and exciting. The other finding revealed the increase in vocabulary mastery. It was shown by the increase in score from 54.6 in post test of cycle one to 79.14 in the post test of cycle 2.  Therefore, it can be concluded that the use of word cross game improved the students’ vocabulary learning.